Proceedings of the International Conference on Research and Academic Community Services (ICRACOS 2019) 2020
DOI: 10.2991/icracos-19.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Indonesia Coffee Exports Volume

Abstract: This study aimed to analyze factors influencing coffee exports volume in Indonesia. The study belonged to quantitative research with secondary data of time series in the period of 1983-2017. For more, the technique of analysis employed in this study was Multiple Linear Regression Analysis with Ordinary Least Square (OLS) method using Eviews 10 software. Based on the findings derived from multiple linear regression analysis, it could be concluded that the variable of domestic coffee production partially contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…With the increase in the coffee market in Indonesia (Prajanti et al, 2020), it is important to study the effects that a possible intensification in crop management can produce. Indonesia has been particularly affected by a reduction of remnant forest and the subsequent shift to agriculture, therefore, promoting sustainable agriculture is crucial also considering the steep increase of the human population (Jha et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in the coffee market in Indonesia (Prajanti et al, 2020), it is important to study the effects that a possible intensification in crop management can produce. Indonesia has been particularly affected by a reduction of remnant forest and the subsequent shift to agriculture, therefore, promoting sustainable agriculture is crucial also considering the steep increase of the human population (Jha et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is a big gap in the literature, especially considering that Indonesia is not only the fourth largest coffee producer in the world (Szenthe, 2020) but also a global biodiversity hotspot (von Rintelen et al, 2017). Coffee production in Indonesia has increased since 2010, both in terms of local and exported coffee markets (Nopriyandi & Haryadi, 2017;Prajanti et al, 2020). With the increase in these markets, it is plausible to expect an intensification in the management of coffee fields, the consequent reduction of shade-grown coffee and the increased use of chemicals.…”
mentioning
confidence: 99%
“…The relationship between export volume and production also international prices itself can be illustrated from that theory where when the supply of production or international prices increases, exports will also increase. Prajanti et al, (2020) In his research, it proves that partially the production variables have a positive and significant effect on the volume of Indonesian coffee exports. Siburian, (2014) on the other side, stated that when the international rubber price increases, Indonesian rubber exporters will carry out greater production to increase export value.…”
Section: Introductionmentioning
confidence: 95%
“…According to Elisha (2015), the Indonesia coffee yield exported to the United States had a positive and significant impact in the short-run and long-run for 33 years (1981 until 2013). Prajanti et al (2020) reported that Indonesia coffee yield significantly affected the coffee export. Desnky et al (2018) stated that the coffee yield experienced an average growth of 2.11% and affected the coffee export for 16 years (2000 until 2015) to the United States.…”
Section: Selection Modelmentioning
confidence: 99%